2018
DOI: 10.15694/mep.2018.0000237.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reflective Writing on Burnout in Medical Trainees

Abstract: Introduction: Narrative Perspective and Reflective Writing is a fourth-year elective at the Donald and Barbara Zucker School of Medicine at Hofstra/Northwell. This is the first study to show through both quantitative and qualitative data that medical students who participated in such a course experienced lower burnout. Preliminary data suggests that the course also fostered increased resilience. Methods: This longitudinal course was offered to all fourth-year medical students as an elective. Assessments were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…Our analysis further revealed that study participants discussed both the positive and negative effects of medical students' empathic engagement with patients and their stories and included nuanced perspectives on the structural causes of burnout, including depersonalization and imposter syndrome. Self-reflective writing normalizes discussion of empathic conflicts, which has been shown to be critical for building resilience and combating burnout in health professionals (Chen and Forbes 2014;Narayan, Stern, and Fornari 2018;Harscher et al 2018;Pohontsch et al 2018). Our finding that premedical students were able to recognize burnout among their nearpeers, despite not experiencing burnout themselves, may have important educational implications in allowing them to better recognize and prevent burnout in themselves in the future (Jennings 2009).…”
Section: Theme 1: Empathic Conflictmentioning
confidence: 68%
“…Our analysis further revealed that study participants discussed both the positive and negative effects of medical students' empathic engagement with patients and their stories and included nuanced perspectives on the structural causes of burnout, including depersonalization and imposter syndrome. Self-reflective writing normalizes discussion of empathic conflicts, which has been shown to be critical for building resilience and combating burnout in health professionals (Chen and Forbes 2014;Narayan, Stern, and Fornari 2018;Harscher et al 2018;Pohontsch et al 2018). Our finding that premedical students were able to recognize burnout among their nearpeers, despite not experiencing burnout themselves, may have important educational implications in allowing them to better recognize and prevent burnout in themselves in the future (Jennings 2009).…”
Section: Theme 1: Empathic Conflictmentioning
confidence: 68%